2018
DOI: 10.1371/journal.pbio.2004411
|View full text |Cite
|
Sign up to set email alerts
|

Role of the AP-5 adaptor protein complex in late endosome-to-Golgi retrieval

Abstract: The AP-5 adaptor protein complex is presumed to function in membrane traffic, but so far nothing is known about its pathway or its cargo. We have used CRISPR-Cas9 to knock out the AP-5 ζ subunit gene, AP5Z1, in HeLa cells, and then analysed the phenotype by subcellular fractionation profiling and quantitative mass spectrometry. The retromer complex had an altered steady-state distribution in the knockout cells, and several Golgi proteins, including GOLIM4 and GOLM1, were depleted from vesicle-enriched fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(145 citation statements)
references
References 61 publications
6
138
0
1
Order By: Relevance
“…Clathrin coat is composed of clathrin heavy and light chains and one of several adaptor complexes and functions in anterograde trafficking from the Golgi, retrograde trafficking from PM, as well as trafficking between endosomes and other compartments . The clathrin coat works with several different classes of adaptor proteins to give a specificity for packaging of these vesicles .…”
Section: Intracellular Membrane Trafficking Pathways and Machinerymentioning
confidence: 99%
“…Clathrin coat is composed of clathrin heavy and light chains and one of several adaptor complexes and functions in anterograde trafficking from the Golgi, retrograde trafficking from PM, as well as trafficking between endosomes and other compartments . The clathrin coat works with several different classes of adaptor proteins to give a specificity for packaging of these vesicles .…”
Section: Intracellular Membrane Trafficking Pathways and Machinerymentioning
confidence: 99%
“…For our publications (see Davies et al, 2018;Itzhak et al, 2016, 2017, Hirst, Itzhak, Antrobus, Borner, & Robinson, 2018, the SIMCA software package was used for PCA (Fig. In order to reduce the dimensionality of the data, principal component analysis (PCA) is applied.…”
Section: Visualization Of Results With Principal Component Analysis (mentioning
confidence: 99%
“…Accordingly, we found a clear reduction of nanobody sulfation upon knockdown of Vps26, confirming the role of retromer in retrograde transport also for CDMPR. There are many reports for a requirement of retromer for CIMPR (Arighi et al, 2004;Bugarcic et al, 2011;Bulankina et al, 2009;Chen et al, 2019;Cui et al, 2019;Fjorback et al, 2012;Hao et al, 2013;Harbour et al, 2010;Hirst et al, 2018;McGough et al, 2014;Seaman, 2004;Seaman, 2007;Seaman et al, 2009;Seaman, 2018;Wang et al, 2018;Wassmer et al, 2007). However, the requirement of the trimeric Vps retromer complex for CIMPR retrieval has recently been challenged by reports of the Cullen and Steinberg labs (Kvainickas et al, 2017;Simonetti et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have analyzed the contribution of individual sorting machineries in retrograde endosome-to-TGN transport of CDMPR and found that several machineries contribute, likely from different types of endosomes: retromer, the clathrin adaptors AP-1, epsinR, and -most surprisingly -the GGAs, and to some extent Rab9. Other sorting machineries that might facilitate endosome-to-TGN transport of CDMPR include SNX-BAR proteins and AP-5 (Hirst et al, 2018;Kvainickas et al, 2017;Simonetti et al, 2017;Simonetti et al, 2019). Both have been shown to be important for CIMPR retrieval, not yet for CDMPR.…”
Section: Discussionmentioning
confidence: 99%